Training Entrepreneurs: The Impact of Tafarkin Tsira Islamic Centre Azare in Bauchi State Nigeria - Idris Abubakar Talle; Bala Babangida; Adamu Abubakar Muhammad (Universitas Darussalam Gontor, 2024)
Entrepreneurship has the power to change lives and communities in a current global economic challenge, training the entrepreneurs to maintain the situation is a priority of institutions and Tafarkin Tsira Islamic Centre Azare in Bauchi State Nigeria is a prime example. This center has been training and counseling entrepreneurs for years, providing them with the creative and management skills as well as relevant support they need to launch successful businesses. Through its various programs and initiatives, the Tafarkin Tsira Islamic Centre Azare is transforming the economic landscape of the citizens in the region and creating a brighter future for its people. This research, will explore the impact of the center on the community, highlighting the success stories of entrepreneurs who have benefited from its programs. The study employed the qualitative method for gathering data through literature review and interview with pertinent people and used content analysis for analyzing the data. It is recommended that no meaningful entrepreneurship skills are attained without mentorship, and training and practice remained as powerful tools of any success. It is also discovered that the power of entrepreneurship and the role of Tafarkin Tsira Islamic Centre Azare in shaping a new generation of successful business owners in the region helped in reshaping enterprises practice.